Geographical variation in the bill patterns of Whooper Swans - Brazil, M A (Wildfowl, 1981)
Field observations in Britain, Iceland and Japan showed that Whooper Swans Cygnus c. cygnus at the eastern end of their range have more yellow on their bills than do those at the western extreme. While the bill patterns of Bewick's C. columbianus bewickii and Whistling Swans C. columbianus columbianus are most similar where their ranges are closest, those of the Whooper and Trumpeter Swans C. c. buccinator are then most different. The latter pair may have diverged earlier or have remained more consistently isolated.